Voluntary conversion of convertible securities and the optimal call strategy - Dunn, Kenneth B.; Eades, Kenneth M. (Journal of Financial Economics, 1989)
We provide an explanation of why convertibles are called long after the conversion value exceeds the call price. Delaying the call benefits the firm if enough investors are expected to delay their voluntary conversions. Consistent with this theory, we document that a substantial number of investors do not voluntarily convert when the common dividend exceeds the convertible's dividend plus its premium over conversion value. We find that firms would not have increased common stock returns by switching to the strategy of calling to force conversion as soon as possible. Surprisingly, we find that convertible preferreds frequently sell below conversion value.